Respuesta :
Answer: X = 24
Step-by-step explanation:
Move all terms to the left:
(3x + 10) - (2x - 9) - 43 = 0
Get rid of all the parenthesis:
3x + 10 - 2x - 9 - 43 = 0
Add all the numbers and all variable:
x-24 = 0
Move all terms containing x to the left and all other terms to the right:
x = 24
Answer:
x = 24
Step-by-step explanation:
Simplify
( 3 x +10 ) − ( 2 x − 9 )
Simplify each term.
Apply the distributive property.
3 x + 10 − ( 2 x)− = 43
Multiply 2 by − 1 .
3 x + 10 − 2 x − − 9 = 43
Multiply − 1 by − 9 .
3 x + 10 − 2 x + 9 = 43
Simplify by adding terms.
Subtract 2 x from 3 x .
x + 10 + 9 = 43
Add 10 and 9 .
x + 19 = 43
Move all terms not containing x to the right side of the equation.
Subtract 19 from both sides of the equation.
x = 43 − 19
Subtract 19 from 43 .
x = 24